(untitled) (Szociológiai Szemle, 2024)
The paper was written on the basis of data collection by questionnaire done in 1980 and 1989 in identical populations (in two graduate cohorts of men who completed their studies at the day courses of the Technical University of Budapest). The paper surveys the changes of engineers’ incomes and satisfaction with them during ten years and it presents the modifications of attitudes related to enterprise. The more pliable attitudes of the 80s were not attached to realities but to desires. Yet those who had seen a more attractive perspective in enterprise, availed themselves of the opportunity and have, by the late 80s either become entrepreneurs, or at least assess free career positively. The two cohorts, because of their different personal history, have shown different features in their behaviour as well as in assessing the economic, social and political crisis. This is also reflected in the set of vies which can be studied from the angle of entrepreneurial versus employee mentality. The paper ends with outlining the political value choices that can be more or less strongly linked to the above mentioned features.